Hamka’s Legal Methodology on Hisab–Ru’yah in His Book “Saya Kembali ke Ru’yah” - Helim, Abdul (JURIS (Jurnal Ilmiah Syariah), 2024)
This research endeavors to explore the contextual shifts in Hamka’s perspectives on hisab-ru’yah and his methodological approach to legal reasoning. It adopts a normative legal research methodology with a conceptual framework. Primary legal sources are drawn from Hamka’s book “Saya kembali ke Ru’yah”. These sources are scrutinized through the lenses of uṣūl al-fiqh and the sociology of knowledge. The findings of this study indicate that the transformation in Hamka’s thinking stemmed from profound childhood experiences and culminated in a notable enlightenment during his participation in the International Islamic Conference in Malaysia. Ultimately, his stance evolved dramatically, concluding unequivocal support for the practice of ru’yah (moon sighting). Furthermore, there are also figures within Muhammadiyah who endorse both ru’yah and istikmāl (completing the lunar month if the moon is not sighted). This support has fortified Hamka despite facing considerable criticism. From the perspective of uṣūl al-fiqh (principles of Islamic jurisprudence), Hamka’s shift in legal reasoning appears primarily theoretical, although he does not explicitly delineate the specific theory involved. This can be inferred from his interpretation of the hadith of ru’yah in alignment with the principles of manṭūq (explicit meaning) or dilālah al-‘ibārah (indicative meaning). In expressing his views, Hamka incorporates the opinions of scholars, indicating his reliance on the qaulī method. His personal joy during fasting and holiday celebrations concurrently reflects his alignment with the maṣlaḥah theory, enhancing unity and cohesion. However, this unity can only be fully realized under government regulation as the ūlīl amr (ruler), particularly concerning the outcomes of ru’yah and istikmāl. Such submission, beyond mere compliance, also falls within the realm of maṣlaḥah al-mu’tabarah (considered public interest). This research underscores the necessity of approaching legal provisions from multiple perspectives, rather than a singular viewpoint, to achieve the intended legal spirit and realize genuine benefits. Hamka’s methodology exemplifies him as a contextual integrative Muslim.